An energy detector in UWB receiver - Guo, Yueyang (Nanyang Technological University, 2023)
This dissertation provides a comprehensive overview of fundamental CMOS technology and RF communication systems. It explores the fundamental components of a non-coherent RF receiver in detail. Additionally, it delves into the circuit structures of an energy-detector and presents analysis of its functionality. Moreover, the dissertation presents the design of a sub-threshold squarer and showcases simulation results demonstrating its effectiveness in performing basic squaring operations on input UWB signals ranging from 3 to 5 GHz.